Advanced imaging techniques applied to the Knossos statuette inscription - Len Gleeson (Heritage Science, 2023)
Abstract The inscription of the statuette from Knossos, Heraklion Archaeological Museum Λ 95, has proven over the years to be exceedingly difficult for the correct identification of its hieroglyphic signs. The signs vary widely in their quality of engraving, with some being so small and shallow that they cannot be recognized at all by traditional techniques, and the stone’s surface shows evidence of ‘staining’ after many centuries of burial in the temperate soil. Furthermore, it appears that some signs were never actually completely engraved, with what appears to be remnants of the original marking paint, now bridging areas of disjoint engravings. Optical Profilometry equipment was employed to unambiguously resolve the engraved parts of the inscription, while Multi-Spectral Imaging was used to identify the areas of remnant marking paint.